Occupational Exposure to Antineoplastic Agents: An Analysis of Health Care Workers and Their Environments. (January 2017) - Graeve, Catherine Utecht; McGovern, Patricia Marie; Alexander, Bruce; Church, Timothy; Ryan, Andrew; Polovich, Martha
Approximately 8 million health care workers are unnecessarily exposed to highly toxic drugs used to treat cancer; antineoplastic drugs can contribute to negative health effects for these workers. The drugs have been detected in the urine of workers and on the floors and counters of worksites. Safety precautions that could reduce the risk of exposure are underutilized. This cross-sectional study of 163 oncology health care workers used a survey to measure workplace and individual factors, and environmental sampling to measure surface contamination. The study objective was to identify potential exposures to antineoplastic drugs and factors influencing safety behavior. Personal protective equipment (PPE) use was lower than recommended; unit of employment was significantly associated with PPE use. Chemical residue from antineoplastic drugs was found, revealing potential exposures. Workplace safety must be a higher organizational priority. The contamination of common work areas where PPE use is not expected was of utmost concern.